How do primary clinics successfully navigate stakeholder partnerships in dynamic healthcare ecosystems? A strategic imperative for leaders - Apriza, Sari; Kuncoro, Engkos Achmad; Alamsjah, Firdaus; Furinto, Asnan (Frontiers in Communication, 2025)
Indonesia’s healthcare sector is growing rapidly and facing increasingly fierce competition from new players and disruptive trends. In this dynamic environment, primary clinics must strengthen partnerships with stakeholders to build a foundation for resilience and sustainable growth. This study examines the influence of partnership capacity and collaborative leadership on stakeholder partnerships and analyzes the moderating role of a dynamic health ecosystem in the context of primary clinics in Indonesia. Using survey data collected from 370 clinic leaders, this study applies partial least squares structural equation modeling (PLS-SEM) with SmartPLS (version 4.1.1.4) to test the research hypotheses. The results indicate that partnership capacity and collaborative leaders have a significant positive influence on stakeholder partnerships, while a dynamic health ecosystem significantly weakens this relationship. The research model explains 64% of the variance (R2 = 0.64) in stakeholder partnerships, demonstrating strong explanatory power consistent with previous studies in health and management. These findings highlight the strategic importance of leaders adopting a collaborative leadership style to complement institutional partnership capacity. In practice, partnership capacity provides the structural foundation for collaboration, while collaborative leadership transforms trust, communication, and adaptability into effective stakeholder engagement. Together, these factors strengthen clinics’ ability to navigate uncertainty in Indonesia’s dynamic healthcare ecosystem.